Iraq : Selected Issues. (IMF Staff Country Reports; Country Report, 2013)
This Selected Issues paper on Iraq discusses medium-term projections for oil production and exports. Constraints to oil export volumes arise from export bottlenecks and technical production issues. Production is held back by technical challenges such as the need for water injection in the southern oil fields and limited supply of electricity, of which the oil industry is one of the main consumers. Export infrastructure has suffered during many years of decay owing to sanctions and wars. The Iraqi crude is priced as an average of a benchmark oil price for 15 or 30 days from the bill of lading.